# <span lang="EN-US

Let us assume Adding – 1 and + 1    Let  Thus I = I1 – I2 …….equation 1

Solving for I1  since I1 = [tan – 1(∞) – tan – 1(0)]

I1 = π/2 ……….equation 2

Solving for I2 Let .....…..equation 3  a + b = 0; a + c = 1; b + c = 0

solving we get

a = c = 1/2

b = – 1/2

substituting the values in equation 3  Thus substituting the values in I2, thus  Solving : Let 1 + x2 = y

2xdx = dy

For x = ∞

y = ∞

For x = 0

y = 0

substituting values  Thus   ……….equation 4

Substituting values equation 2 and equation 4 in equation 1

Thus

I = I1 – I2

I = π/2 – π/4

I = π/4

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

<span lang="EN-USRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2